A sensitive electrochemical platform integrated with a 3D graphene aerogel for point-of-care testing for tumor markers. Issue 36 (19th August 2022) - Hu, Tao; Wu, Zihao; Sang, Wen; Ding, Bo; Chen, Ke; Li, Xiao; Shen, Yang; Ni, Zhonghua
Abstract : A detection platform based on electrochemical biosensor with high sensitivity and a low detection limit for tumor markers was developed, which used the graphene aerogel with high specific surface area and biocompatibility as the electrode material. Abstract : Point-of-care testing (POCT) of tumor markers, such as alpha-fetoprotein (AFP) and carcinoembryonic antigen (CEA), can be used for the early diagnosis of cancer. In this paper, a highly sensitive electrochemical immuno-biochip based on a porous three-dimensional graphene aerogel (3D-GA) is presented to detect multiple tumor biomarkers and exosomes. The 3D-GA was prepared via in situ chemical reduction of graphene oxide with l -ascorbic acid and then dehydration by freeze-drying. The obtained 3D-GA exhibits a large specific surface area of 125.3 m 2 g −1 due to its intrinsic 3D porous architecture. After chemical activation and modification of the 3D-GA, the prepared microfluidic biochip can be used for detecting various tumor markers in liquid samples via electrochemical impedance spectroscopy (EIS). The electrochemical platform with only 5 μL sample achieved a broad detection range of 1.0 × 10 −8 –1.0 × 10 −5 and 1.0 × 10 −8 –5.0 × 10 −4 mg mL −1 for AFP and CEA, respectively, and a low limit of detection (LOD) of 7.9 and 6.2 pg mL −1 for AFP and CEA respectively, which was much better than the outcomes of many other reports. Moreover, the biochip determined the tumor cell-derived exosomes with a low LOD of 10 particles per μL in the PBS solution and an average recovery rate of ∼90% in the diluted serum.